Hedging Energy Security through Infrastructure Diplomacy: The Pursuit of Economic Sovereignty in Azerbaijan-Indonesia Energy Cooperation Post-COP29 - Nadila Putri Shenindita (Green Publisher Indonesia, 2026)
In the wake of COP29 in Baku, the geopolitical landscape of energy has transitioned toward a